A case of bilateral stellate nonhereditary idiopathic foveomacular retinoschisis with 14-month follow-up: clinical features, OCT findings and treatment outcome - Narges Hassanpoor; Ali Tahmasebi; Ehsan Aminsobhani; Mohamadreza Niyousha (BMC Ophthalmology)
Abstract Background Stellate nonhereditary idiopathic foveomacular retinoschisis (SNIFR) is a relatively recent and rare classification introduced. Currently, there is no reliable treatment for the disease. Case presentation We discussed an additional case multimodal imaging including Optical coherence tomography (OCT), fluorescein angiography and Optical coherence tomography angiography (OCTA) as well as treatment result. The case was a healthy, non-myopic woman, where foveal cystic changes persisted despite 9 months of topical dorzolamide and an additional 5 months of oral acetazolamide. Genetic testing for Congenital X-linked retinoschisis (CXLR) was negative. ERG results were near normal. Optical coherence tomography showed no vitreomacular traction, while fluorescein angiography ruled out vascular disease. Conclusions Our findings suggest that bilateral SNIFR can occur in non-myopic females, although this patient did not respond to systemic and topical carbonic anhydrase inhibitors.